2010
DOI: 10.1007/jhep07(2010)056
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Roberge-Weiss transitions

Abstract: We investigate N = 4 SYM coupled to fundamental flavours at nonzero imaginary quark chemical potential in the strong coupling and large N limit, using gauge/gravity duality applied to the D3-D7 system, treating flavours in the probe approximation. The interplay between Z N symmetry and the imaginary chemical potential yields a series of first-order Roberge-Weiss transitions. An additional thermal transition separates phases where quarks are bound/unbound into mesons. This results in a set of Roberge-Weiss endp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Results have first been obtained within a staggered fermion formulation of QCD, but efforts have been undertaken to confirm their universality also within a Wilson fermion approach [35,[37][38][39] leading to the same qualitative phase diagram [35]. The Roberge-Weiss endpoint transition, or variants of it, also has been studied in many other different contexts and QCD-like theories [40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Phase Diagram For Imaginary Chemical Potentialmentioning
confidence: 99%
“…Results have first been obtained within a staggered fermion formulation of QCD, but efforts have been undertaken to confirm their universality also within a Wilson fermion approach [35,[37][38][39] leading to the same qualitative phase diagram [35]. The Roberge-Weiss endpoint transition, or variants of it, also has been studied in many other different contexts and QCD-like theories [40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Phase Diagram For Imaginary Chemical Potentialmentioning
confidence: 99%
“…ii) Early studies have shown that the RW endpoint transition is first order for small quark masses, second order for intermediate masses, and again first order for large masses; the three regions are separated by two tricritical points [13][14][15]. The emergence of this interesting structure has induced many further studies in effective models [28][29][30][31][32][33][34][35][36][37][38][39][40] which try to reproduce the essential features of QCD. Moreover, interesting proposals have been made on the connection of this phase structure with that present at µ B = 0 (the so-called Columbia plot) and on the possibility to exploit the whole phase structure at imaginary chemical potential in order to clarify currently open issues on the phase structure at µ B = 0, like the order of the chiral transition for N f = 2 [21,24].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the standard definition of electric and magnetic screening masses could be maintained; however, it is well known that for such special values of θ charge conjugation undergoes a spontaneous breaking above some critical temperature [55], which is usually known as the Roberge-Weiss transition temperature T RW and has been investigated in many lattice [56][57][58][59][60][61][62][63][64][65][66][67] and model [68][69][70][71][72][73][74][75][76][77][78][79] studies. For T > T RW , the spontaneous breaking induces a mixed electric-magnetic correlator, so one needs to extend the definition of the gauge-invariant screening masses as discussed above.…”
Section: Observables and Numerical Methodsmentioning
confidence: 99%